Africa's Pulse, No. 15, April 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Economic growth in Sub-Saharan Africa is projected to recover to 2.6 percent in 2017, following a marked deceleration in 2016. The upturn in economic activity is expected to continue in 2018-19, reflecting improvements in commodity prices, a pickup in global growth, and more supportive domestic conditions. The pace of the recovery remains weak, however, as the region's three largest economies – Angola, Nigeria, and South Africa – are projected to post only a modest rebound in growth following a sharp slowdown in 2016. Investment growth will recover only gradually, amid tight foreign exchange liquidity conditions in major oil exporters and low investor confidence in South Africa. Growth will be limited in several metals exporters, as well as in oil exporters in the Central African Economic and Monetary Community, as these countries embark on fiscal adjustment to stabilize their economies. Among non-resource intensive countries, such as Ethiopia, Senegal, and Tanzania, growth is expected to remain generally solid, supported by domestic demand.